Biological aspects and control of a Gracillariidae (Gracillariidae: Lepidoptera) in Caesalpinia spinosa (Mol.) Kuntze (1898), in Cajamarca, Peru - Murga, Hipólito (2016)
Determine biological target, identify natural enemies, and establish appropriate periods of controlling a pest gracillariid tare. The biological aspects and natural enemies in field and laboratory were evaluated, appropriate control periods was determined by host-pest interaction. The results, egg lasts 7.8 days and measured 0.34x0.21 mm; presents four instars larvae and lasts 35.7 days, ranging from measures between 1st and the 4th instar from 0.09 to 0.65 mm diameter brain; the pupa lasts 14.3 days and measured 6.7mmx1.1mm; adult takes 7.5 days and measured 13.43 mm wingspan. Presents natural enemies, family Encyrtidae, Ichneumonidae, and genres Chelonus sp., Chrysoperla sp., Hemerobius sp., Cicloneda sp., Hippodamia sp., and Zelus spp. The best times control occur when the phenology of the tara is between R3.1 to R3.3 and R4 to R6.